PENGARUH METODE BERCERITA DENGAN MEDIA BUKU CERITA BERGAMBAR TERHADAP KEMAMPUAN BERBAHASA PADA ANAK KELOMPOK B DI TK INFARUL GHOY 1 TRITUNGGAL, BABAT, LAMONGAN - Yani Ayu Dwi Putri; Ervin Nurul Affrida (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
Early Childhood Education (PAUD) is an effort to foster children from birth to 6 (six) years of age. Through PAUD, it is expected that children can develop all their potential. One of the developments that needs to be honed is children's language skills. The development of language skills aims for children to be able to express their thoughts through simple language by telling stories appropriately and being able to communicate effectively. In this study, we will discuss how the storytelling method using picture story books can improve language development in early childhood. The results of the study showed an average increase where at the time of the pre-test the average language ability of students was 5.08, and at the time of the post-test it became 8.48 where there was an increase of 3.40. This is one of the efforts to improve the language skills of early childhood through the storytelling method as has been applied by researchers.